Coronally repositioned flap with and without connective tissue graft to treat gingival recession - Rocio Alvarez-Medina; Claudia Anco-Valencia; Claudia Romero-Reyes; Judit Bermudez-Mendoza; Pedro Luis Tinedo-López (Editorial Ciencias Médicas, 2022)
Introduction: Gingival recession is a very common gum condition which may result in aesthetic alterations and dentin hypersensitivity, and increase the probability of cervical lesions. It is necessary to cover the root surface using periodontal regeneration techniques. Objective: Compare the amount of root coverage, probing depth and clinical insertion level, using coronally repositioned flap techniques with and without connective tissue graft in patients with Miller I and II gingival recessions. Methods: A total 16 patients with Miller class I and II gingival recessions were included in the study, from whom 50 teeth were selected which had been treated surgically to cover the recessions. The techniques used were coronally repositioned flap with and without connective tissue graft. Clinical measurements were compared at the start of the postoperative period and three months later. Results: Three months after surgery, root coverage, probing depth and clinical insertion level were 0.96 ± 1.33; 0.87 ± 0.63; 1.83 ± 1.7, respectively, for coronally repositioned flap with connective tissue graft, and 1.44 ± 1.19; 1.04 ± 0.52; 2.48 ± 1.48, respectively, for coronally repositioned flap. Root coverage intergroup comparison did not find any significant differences (p = 0.11). However, intergroup comparison of probing depth (p = 0.04) and clinical insertion level (p = 0.001), and all the intragroup clinical measurements (p = 0.001) did find significant differences. Conclusions: Coronally repositioned flap technique with and without connective tissue graft showed significant differences in terms of probing depth and clinical insertion level in Miller I and II gingival recessions. At three months' follow-up, no root coverage significant differences were observed for either technique.